Audit Sistem Informasi Portalsia Menggunakan Framework Cobit 5 Pada EDM05, APO04 dan BAI10 - Esa Surya Anggraini; Muhammad Aprilsyah; Inneke Nugroho Hasibuan; Lili Asisura; Chairul Rizal (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2024)
COBIT 5 (Control Objectives for Information and Related Technology) is a framework that provides comprehensive guidance for the governance and management of information technology. This research aims to assess the effectiveness and efficiency of the PortalSIA information system at the North Sumatra State Islamic University using the COBIT 5 framework. In this audit, we used a qualitative descriptive analysis method which involved collecting data through interviews, questionnaires and documentation. The results of this audit were prepared based on the COBIT 5 domain, which includes evaluation, direction, monitoring (EDM), alignment, planning and organizing (APO) and development, acquisition and implementation (BAI). By implementing the recommendations from this audit, it is hoped that the North Sumatra State Islamic University can improve the performance and security of the PortalSIA information system, as well as achieve its strategic goals more effectively and efficiently. This research also emphasizes the importance of regular audits and the use of frameworks such as COBIT 5 in improving the quality of governance and information technology management in higher education institutions.